miR-185-5p / ATG101 axis alleviated intestinal barrier damage in intestinal ischemia reperfusion through autophagy - Wendong Chen; Li Ma; Jianlin Shao; Chun Bi; Junjie Li; Wei Yang (Heliyon, 2023)
Objective: Intestinal ischemia-reperfusion (II/R) is a common pathological injury in clinic, and the systemic inflammatory response it causes will lead to multiple organ damage and functional failure. miR-185-5p has been reported to be a regulator of inflammatory response and autophagy, but whether it participates in the regulation of autophagy in II/R is still unclear. Therefore, we aimed to explore the mechanism of miR-185-5p regulating intestinal barrier injury in (II/R). Methods: Caco-2 cells was induced by oxygen-glucose deprivation/reoxygenation (OGD/R) to establish II/R model. The superior mesenteric artery of C57BL/6 mice was clamped for 45 min and then subjected to reperfusion for 4 h for the establishment of II/R mice model. miR-185-5p mimic, miR-185-5p inhibitor, pcDNA-autophagy-related 101 (ATG101) were respectively transfected into Caco-2 cells. Real-time quantitative polymerase chain reaction (RT-qPCR) was performed to assess miR-185-5p expression. Western blot detected the level of ATG101 and tight junction-associated proteins ZO1, Occludin, E-cadherin, β-catenin, as well as autophagy markers ATG5, ATG12, LC3Ⅰ/Ⅱ, Beclin1 and SQSTM1. Transepithelial electrical resistance (TEER) values was detected by a resistance meter. FITC-Dextran was performed to measure cell permeability. 5-ethynyl-2’-deoxyuridine (EDU) staining measured cell proliferation. Transmission electron microscope was conducted to observe autophagosomes. Hematoxylin & eosin (H&E) staining observed the damage of mice intestinal. Immunohistochemistry (IHC) measured the percentage of ki67 positive cells. TdT-mediated dUTP nick-end labeling (TUNEL) assay assessed cell apoptosis in intestinal tissues of II/R. Dual-luciferase assay verified the targeting relationship between miR-185-5p and ATG101.Results miR-185-5p was overexpressed in OGD/R-induced Caco-2 cells and intestinal tissues of II/R mice. Knocking down miR-185-5p markedly promoted autophagy and TEER values, reduced cell permeability, and alleviated intestinal barrier damage. ATG101 was a target of miR-185-5p, and overexpression of ATG101 promoted autophagy and dampened OGD/R-induced intestinal barrier damage. Overexpression of miR-185-5p reversed the effect of overexpressed ATG101 on OGD/R-induced Caco-2 cells. Conclusion: Knockdown of miR-185-5p enhanced autophagy and alleviated II/R intestinal barrier damage by targeting ATG101.